Floral nectaries in sapindaceae s.s. : morphological and structural diversity, and their systematic implications - Solís, Stella Maris (2017)
Fil: Solís, Stella Maris. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.